2014
DOI: 10.1080/01425692.2014.883274
|View full text |Cite
|
Sign up to set email alerts
|

Between returns and respectability: parental attitudes towards girls’ education in rural Punjab, Pakistan

Abstract: The accuracy of the Content should not be relied upon and should be independently verified with primary sources of information. Taylor and Francis shall not be liable for any losses, actions, claims, proceedings, demands, costs, expenses, damages, and other liabilities whatsoever or howsoever caused arising directly or indirectly in connection with, in relation to or arising out of the use of the Content. This article may be used for research, teaching, and private study purposes. Any substantial or systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Moreover, another study conducted in southern Punjab, Pakistan also verified the results that there were (60.5%) teachers, (52%) students and (17%) parents agreed that gender discrimination was the key obstacle in the educational inclusion of children (Sattar, Yasin & Afzal, 2012). It was also found that if the poor households got a chance to educate their children, sons were their choice because they considered that sons would look after them in their old age, and daughters would leave home after marriage (Oxaal, 1997;Hashmi, 2015).…”
Section: ___________________________________________________________________________mentioning
confidence: 58%
See 1 more Smart Citation
“…Moreover, another study conducted in southern Punjab, Pakistan also verified the results that there were (60.5%) teachers, (52%) students and (17%) parents agreed that gender discrimination was the key obstacle in the educational inclusion of children (Sattar, Yasin & Afzal, 2012). It was also found that if the poor households got a chance to educate their children, sons were their choice because they considered that sons would look after them in their old age, and daughters would leave home after marriage (Oxaal, 1997;Hashmi, 2015).…”
Section: ___________________________________________________________________________mentioning
confidence: 58%
“…The current research showed that there was a significant relationship was found (X 2 =65.126 a ), (P=.000) between the parents' attitude that limited financial resources families gave priority to sons' education, not daughter's education and the educational ___________________________________________________________________________ exclusion of the children. It was highlighted by Hashmi(2015)that 52 percent of household heads preferred male children over female children. Moreover, another study conducted in southern Punjab, Pakistan also verified the results that there were (60.5%) teachers, (52%) students and (17%) parents agreed that gender discrimination was the key obstacle in the educational inclusion of children (Sattar, Yasin & Afzal, 2012).…”
Section: ___________________________________________________________________________mentioning
confidence: 99%
“…While such considerations were important among upper caste and elite groups earlier, the studies reveal that they have emerged strongly even in the case of groups that have only recently begun to access education for their girls (Still 2011). An empirical study to understand the determinants of parental choice with regard to their children's education in some parts of rural Pakistan revealed that the dominant taxonomy that was applied to decisions about girls' education was in terms of "returns" and "respectability" (Purewal and Hashmi 2014). Similar considerations are evident from the ethnographic study of Dalit families in a southern state of India (Still 2011) and among low income families in a Muslim-dominated village also in South India (Roy 2015).…”
Section: Sociocultural and Economic Factorsmentioning
confidence: 82%
“…Girls' agency, derived from education, allows them to pose a challenge to social norms; at the same time rising aspirations of parents for daughters reveal a willingness to subvert or manipulate social norms that come in the way, as in the case of girls moving to other cities for education or taking up call centre work that requires working night shifts (Tara and Vigneswara Ilavarasan 2009). Daughters are also being increasingly contrasted with "worthless" sons who are unable to fulfil their filial duties of economic and affective support towards parents and shifting expectations of greater reliance on support from daughters, even married ones (Croll 2006;Purewal and Hashmi 2015;John 2018).…”
Section: Shifting Parental Attitudes: Investing In Daughters' Educationmentioning
confidence: 99%